Appropriate Assessment Criteria to the Prototype Area for Quality of Life According to the New Theory, Applied to the “Khok Nong Na Model” - Hanphakdeeniyom, Anitta; chaiwong, Silawat (Journal of Management Science Nakhon Pathom Rajabhat University, 2023)
The objectives of this research were 1) to study the factors of the prototype area for quality of life according to the New Theory, applied to the “Khok Nong Na Model”, and 2) to provide assessment criteria to the prototype area for quality of life according to the New Theory, applied to the “Khok Nong Na Model” and 3) study guidelines, problems and obstacles in the prototype area for quality of life according to the New Theory, applied to the “Khok Nong Na Model”This study used mix-method research. For the quantitative research, the sample group included 164 people. Data were collected by questionnaire and analyzed with descriptive statistics. For the qualitative research, 15 key informants, including Executives at department/province/district level responsible government officers, landlords and people in the area. The instruments were in-depth interview. Data ware analyzed by content analysis The results revealed that the activities including 1) the factors of the prototype area for quality of life according to the New Theory, applied to the “Khok Nong Na Model” As for the overall criteria assessment results 4 consisting of social, knowledge, be it area and process it was at a high level (2) to provide assessment criteria to the prototype area for quality of life according to the New Theory, applied to the “Khok Nong Na Model” that is important consisting of 5 consisting 20 measure of Place, People, Product, Promotion and Management 3) guidelines, problems and obstacles in the prototype area for quality of life according to the New Theory, applied to the “Khok Nong Na Model to lack of knowledge don’t skilled personnel about area design. The impact of Natural Disasters including period of time inconsistent with the excavation period to complete. The suggestion is, there should be supervision, monitoring, and long-term Data support to develop and expand the activities in the area according to the social landscape for completeness and sustainability. Article history: Received 27 November 2022 Revised 7 February 2023 Accepted 9 February 2023 SIMILARITY INDEX = 5.74 %